2021
DOI: 10.47316/cajmhe.2020.1.2.06
|View full text |Cite
|
Sign up to set email alerts
|

The Peer Review Process in Asia

Abstract: Peer reviewers are the custodians of sciences and scientific publishing. Previously regarded as a purely altruistic work, with the advent of Publons and Peer Review Week initiatives, reviewers can now get scholarly credits for their accomplishments. The number of skilled peer reviewers is limited. The sheer volume of published literature in today’s world calls for active involvement of a large corpus of reviewers. Asia has a growing workforce of biomedical researchers and scientific authors who are inadequatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…We have described the potential of upcoming researchers and academicians from Central Asia [21,22]. Incorporating medical humanities can help them further develop another unique dimension that can help them in both their academic and patient-centric activities.…”
Section: Current Medical Education: Is It Moving Away From Medical Humanities?mentioning
confidence: 99%
“…We have described the potential of upcoming researchers and academicians from Central Asia [21,22]. Incorporating medical humanities can help them further develop another unique dimension that can help them in both their academic and patient-centric activities.…”
Section: Current Medical Education: Is It Moving Away From Medical Humanities?mentioning
confidence: 99%
“…Things have changed in the last decade with reviewers getting credit for their work on online platforms such as Publons [3]. The peer reviewers from Asia have been discussed previously [4,5]. Academia and researchers from Central Asia are taking a stride forward [6].…”
Section: Introductionmentioning
confidence: 99%
“…An assessment of articles in predatory journals indicated that a considerable portion of the articles was sourced from researchers in Asia and Africa with low experience, and non-native English speakers [10]. The education systems of most Asian countries place limited emphasis on research methods and insufficient focus on the process of producing and publishing a scientific paper [11]. From this perspective, the focus is on Kazakhstan, one of the Central Asian countries, and the following main points are investigated:…”
Section: Introductionmentioning
confidence: 99%